ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PURCHASE BEHAVIOUR PRODUK AC HEMAT LISTRIK DI KOTA BATAM - Christiarini, Renny (Journal of Global Business and Management Review, 2020)
This research was conducted to find out the factors influencing purchase behavior. The independent variables in this study were environmental concern, personal norm, perceived value, and willingness to pay. The intervening variable was purchase intention and the dependent variable is purchase behaviour. The samples in this study were purchasers repurchasing environmentally friendly Air Conditioners under the Sharp, Daikin, Panasonic, LG and Samsung brands. The data were distributed 310 sets. The data received were 307 sets. In this study, the sampling method used by researchers is purposive sampling. After conducting research, research data indicate that environmental concern does not have significant value in this study therefore this variable must be excluded in this study. Personal norm, perceived value, and willingness to pay have significant positive effect on purchase intention. Purchase intention has significant positive effect on purchase behaviour.